Iguratimod as an alternative therapy for systemic sclerosis and prevention of the occurrence of ischemic digital ulcer - Yan, Qingran; Liu, Bei; Wang, Jieying; Yin, Hanlin; Li, Qianqian; Lu, Liangjing (Frontiers in Medicine, 2023)
Objectives This study aimed to assess the effectiveness of iguratimod (IGU) as an alternative treatment for systemic sclerosis (SSc), especially in the prevention of ischemic digital ulcers (DUs). Methods We constructed two cohorts from the Renji SSc registry. In the first cohort, SSc patients receiving IGU were observed prospectively with effectiveness and safety. In the second cohort, we picked up all the DU patients with at least a 3-month follow-up to investigate the prevention of IGU on ischemic DU. Results From 2017 to 2021, 182 SSc patients were enrolled in our SSc registry. A total of 23 patients received IGU. With a median follow-up of 61 weeks (IQR: 15–82 weeks), the drug persistence was 13/23. In total, 91.3% of the patients (21/23) became free of deterioration in the last visit with IGU. Of note, 10 patients withdrew from the study due to the following reasons: two patients withdrew due to deterioration, three due to incompliance, and five due to mild-to-moderate side effects. All the patients with side effects recovered fully after stopping IGU. Of note, 11 patients had ischemic DU, and 8 out of 11 (72.7%) patients had no new occurrence of DU during the follow-up. In the second cohort of 31 DU patients receiving a combination of vasoactive agents with a median follow-up of 47 weeks (IQR, 16–107 weeks), IGU treatment was protective of new DU occurrence (adjusted risk ratio = 0.25; 95% CI, 0.05–0.94; adjusted odds ratio = 0.07; and 95% CI, 0.01–0.49). Conclusion Our study for the first time describes the potential of IGU possibly as an alternative treatment for SSc. To our surprise, this study provides a hint that IGU treatment can be used for the prevention of the occurrence of ischemic DU and merits further investigation.